Nicolas Medtner: His life and music - Martyn, Barrie (Cambridge Scolar Pr, 1995)
This is the biography of Medtner, considering in turn each of his compositions. The author has drawn on Medtner's own correspondence and writings, and has collected the reminiscences of those who knew him personally to build a picture of the composer.